Security and resilience - Business continuity management systems - Requirements - International Organization for Standardization
This document specifies requirements to implement, maintain and improve a management system to protect against, reduce the likelihood of the occurrence of, prepare for, respond to and recover from disruptions when they arise. The requirements specified in this document are generic and intended to be applicable to all organizations, or parts thereof, regardless of type, size and nature of the organization. The extent of application of these requirements depends on the organization's operating environment and complexity. This document is applicable to all types and sizes of organizations that: a) implement, maintain and improve a BCMS; b) seek to ensure conformity with stated business continuity policy; c) need to be able to continue to deliver products and services at an acceptable predefined capacity during a disruption; d) seek to enhance their resilience through the effective application of the BCMS. This document can be used to assess an organization's ability to meet its own business continuity needs and obligations.